Inferência e diagnóstico no modelo espacial linear t-Student reparametrizado: aplicações a dados agrícolas - Schemmer, Rosangela Carline (2021)
This research aims at studying and developing the inference and diagnostic techniques for reparametrized t-Student linear spatial model, with and without replication, applied to data agricultural. Initially, a t-Student distribution reparametrization was carried out, assuming the existence of the second finite moment, with some recurring properties. Analytical expressions were tested for the score function and Fisher matrix of reparameterized distribution. The approach occurred to estimate some parameters, based on the development of an Iterative algorithm. Some criteria were shown to choose the best model by the shape parameter η. A diagnostic analysis was developed to detect the presence of influential observations and possible outliers. These procedures were developed without and with replication. Three papers were written due to the development of this research: diagnosis of influence in a reparameterized t-Student spatial linear model, statistical inference in reparameterized t-Student spatial linear model, reparameterized t-Student spatial linear model with replication. Finally, it can be concluded that reparametrized t-Student linear spatial modeling allows a more robust modeling in the presence of influential observations.